2018
DOI: 10.1039/c8ra01636d
|View full text |Cite
|
Sign up to set email alerts
|

Advantage of semi-ionic bonding in fluorine-doped carbon materials for the oxygen evolution reaction in alkaline media

Abstract: Fluorine-doped carbon has a higher electrocatalytic oxygen evolution activity than pristine carbon black in alkaline media. The activity of oxygen evolution and characteristics of carbon to fluorine bond are controlled by pyrolysis temperature of Nafion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 21 publications
0
37
0
Order By: Relevance
“…The enhanced OER performance after F‐doping was ascribed to the resulting high positive charge on carbon atoms, which could guarantee fast adsorption and exchange of O 2 , OH − , and H 2 O species throughout the OER process. [ 52 ] The electrochemical impedance spectroscopy measurements confirmed that the charge‐transfer resistance ( R ct ) of NPF‐CNS‐2 was much smaller than the IrO 2 and other samples, indicated faster kinetics of the OER for NPF‐CNS‐2 (Figure S27, Supporting Information). A small catalytic degradation was observed in the chronoamperometry ( i – t ) curve for continuous test over 50 000 s, suggesting that NPF‐CNS‐2 had good OER long‐term stability (Figure 5c).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The enhanced OER performance after F‐doping was ascribed to the resulting high positive charge on carbon atoms, which could guarantee fast adsorption and exchange of O 2 , OH − , and H 2 O species throughout the OER process. [ 52 ] The electrochemical impedance spectroscopy measurements confirmed that the charge‐transfer resistance ( R ct ) of NPF‐CNS‐2 was much smaller than the IrO 2 and other samples, indicated faster kinetics of the OER for NPF‐CNS‐2 (Figure S27, Supporting Information). A small catalytic degradation was observed in the chronoamperometry ( i – t ) curve for continuous test over 50 000 s, suggesting that NPF‐CNS‐2 had good OER long‐term stability (Figure 5c).…”
Section: Resultsmentioning
confidence: 96%
“…According to the literature, both of these bonds were associated with high ORR/OER electrocatalytic activity. [26,[51][52][53] Moreover, the surface wettability of the catalysts before and after F-doping was investigated by contact angle measurements ( Figure S12, Supporting Information). The measured contact angles of NP-CNS and NPF-CNS-2 are 70.1° and 27.9°, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The integrated peak area ratio of sp 2 ‐C versus sp‐C is 1.0, in accordance with the chemical composition of p‐FGDY. The fluorine peak (687.4 eV, Figure j) can be ascribed to the semi‐ionic C−F bond with high polarity, which enhances the catalytic activity . This is further verified by our density functional theory (DFT) results (discussed later).…”
Section: Resultsmentioning
confidence: 91%
“…The C-F bonds are formed based on the fluorination reactions between carbon materials and fluorinating agents. Because the F atom has extremely strong electronegativity, fluorinated carbon involves various C-F bonding characteristics of ionic, semi-ionic, and covalent bonds [18][19][20]. Besides, based on theoretical calculation, the C-F bonds depend on the fluorination levels (F/C ratios) [15].…”
Section: Introductionmentioning
confidence: 99%